2020
DOI: 10.1097/md.0000000000023064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical, laboratory, and radiological characteristics between SARS-CoV-2 infection and community-acquired pneumonia caused by influenza virus

Abstract: Coronavirus disease 2019 (COVID-19) is the most important global public health issue that we currently face. We aimed to explore the clinical features of patients with COVID-19 and compared them with those of hospitalized community-acquired pneumonia (CAP) patients caused by influenza virus during the same period. From Jan 1, to Mar 4, 2020, patients with COVID-19 or CAP caused by influenza virus who were admitted to the First Affiliated Hospital of Xiamen University were consecutively screened for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 13 publications
3
20
0
Order By: Relevance
“…In this review, 14 studies of 18 [ 5 , 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 18 , 19 , 20 , 21 ] reported a comparison between COVID-19 and influenza patients based on demographic findings, comorbidities, clinical features, and outcome ( Table 2 ). Fever and respiratory symptoms such as cough, expectoration or sputum production and dyspnea were the main symptoms in both groups with COVID-19 and influenza; however, they were significantly more frequent in patients with influenza [ 5 , 9 , 10 , 11 , 13 , 15 , 16 , 19 , 20 ]. Moreover, vomiting, otorhinolaryngological symptoms such as nasal congestion, rhinorrhea, sore throat and ocular symptoms such as tearing and conjunctival hyperhemia were statistically more frequent in patients with influenza than COVID-19 adult patients [ 5 , 10 , 11 , 12 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this review, 14 studies of 18 [ 5 , 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 18 , 19 , 20 , 21 ] reported a comparison between COVID-19 and influenza patients based on demographic findings, comorbidities, clinical features, and outcome ( Table 2 ). Fever and respiratory symptoms such as cough, expectoration or sputum production and dyspnea were the main symptoms in both groups with COVID-19 and influenza; however, they were significantly more frequent in patients with influenza [ 5 , 9 , 10 , 11 , 13 , 15 , 16 , 19 , 20 ]. Moreover, vomiting, otorhinolaryngological symptoms such as nasal congestion, rhinorrhea, sore throat and ocular symptoms such as tearing and conjunctival hyperhemia were statistically more frequent in patients with influenza than COVID-19 adult patients [ 5 , 10 , 11 , 12 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 studies of 18 [ 7 , 8 , 9 , 10 , 11 , 13 , 14 , 18 , 19 , 20 , 21 ] compared routine laboratory test results between COVID-19 and influenza patients. Both infections caused abnormalities in biological parameters leading to aberrant blood cell counts and sometimes elevated hepatic, renal, and cardiac enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations